Colloidal behavior of aqueous montmorillonite suspensions in the presence of non-ionic polymer. (April 2015) - Gareche, M; Azri, N; Allal, A; Zeraibi, N
Abstract: In this paper we characterized at first, the rheological behavior of the bentonite suspensions and the aqueous solutions of polyethylene oxide (PEO), then we were investigated the influence of this polymer in a water-based drilling fluid model (6% of bentonite suspension). The objective is to exhibit how the non ionic polymer with molecular weight 6×10 3 g/mol. of varying concentration mass (0.7%, 1%, 2% et 3%) significantly alter the rheological properties (yield stress, viscosity, loss and elastic modulus) of the bentonite suspensions. The rheological measurements made in simple shear and in dynamic on the mixture (water-bentonite-PEO), showed rheological properties of bentonite suspensions both in the presence and absence of non-ionic polymer. The PEO presents an affinity for the bentonite particles slowing down their kinetic aggregation. The analysis by X-rays diffraction also allowed understanding the structure of this mixture. It had revealed the intercalation between of the clay platelets on one hand, and the links bridges assured by the chains of polymer between bentonite particles beyond a critical concentration in PEO on the other hand. The Herschel- Bulkley rheological model is used for the correlation of our experimental results.